Facile growth of well-dispersed and ultra-small MoS2 nanodots in ordered mesoporous silica nanoparticles. Issue 67 (8th July 2016) - Wang, Yi; Wang, Shanshan; Li, Chengyi; Qian, Min; Bu, Juan; Wang, Jianxin; Huang, Rongqin
Abstract : Well-dispersed and ultra-small 2H phase MoS2 nanodots were incorporated into MSNs using a facile confined growth method. Abstract : A facile one-step solvothermal method was developed for the homogeneously confined growth of ultra-small (∼1.5 nm) and monodispersed 2H phase MoS2 nanodots into mesoporous silica nanoparticles (MSNs).